Tales of disaster: the role of accident storytelling in safety teaching. Issue 1 (February 2016) - Rae, Andrew
Abstract Is it appropriate to tell tales about accidents as a form of teaching? Storytelling about accidents is an intrinsic part of safety education, but the role and nature of these stories deserves critical consideration. Even accident reports themselves are reconstructed interpretations of events, and accident stories are at least one step further removed. Knowledge about specific accidents is uncertain and unsuitable as a learning outcome. However, accident stories play a role in teaching by creating learning experiences through which students can acquire threshold concepts in safety science. The realism of a well-told story, combined with uncertainty and subjectivity surrounding its interpretation, creates an environment that promotes transformative learning. Narrative choices can make the difference between effective story-based teaching and oversimplified hindsight explanations.